Synthesis, characterization, and biological activity of Cu(II), Ni(II), and Zn(II) complexes of a tridentate heterocyclic Schiff base ligand derived from thiosemicarbazide and 2-benzoylpyridine - Ngoudjou, Line Edwige Tsakeng; Paboudam, Awawou Gbambie; Yepseu, Adrien Pamen; Kuate, Maurice; Doungmo, Giscard; Ndifon, Peter Teke (European Journal of Chemistry, 2022)
Ni(II), Cu(II), and Zn(II) complexes of the tridentate heterocyclic ligand, 2-(phenyl(pyridin-2-yl)methylene)hydrazine-1-carbothioamide (HL) have been synthesized and characterized by various spectroscopic techniques and elemental analyses. Infrared spectroscopy shows that the ligand coordinates to the metal ions through the azomethine and pyridine nitrogen atoms as well as the sulfur atom of the thioamide group to form a tridentate chelate system. In vitro screening of metal complexes against four bacterial strains (Staphylococcus aureus (ATCC 43300), Klebsiella pneumoniae (ATCC 700603), Methicillin resistant staphylococcus aureus (ATCC 33591), Shigella flexneri (NR 518)) and four fungal strains (Candida albicans (NR 29444), Candida albicans (NR 29445), Candida albicans (NR 29451), Candida krusei (HM 1122)) indicate that the Cu(II) complex showed good antibacterial activity on Methicillin resistant staphylococcus aureus (ATCC 33591) while the Zn(II) complex showed moderate activity against some of the bacterial and fungi strains. Antioxidant studies reveal that the complexes are more potent than the ligand to eliminate free radicals, with the Ni(II) complex showing the best free radical scavenger.